(untitled) (Journal of the College of Basic Education, 2022)
The current study was carried out to investigate the effect of age on the levels of thyroid stimulating hormone (TSH), thyroxine (T4), triiodothyronine (T3) and T3-Uptake in normal healthy Females. Serum levels of TSH, T4, T3, and, T3-Uptake were measured in 79 healthy females aged 20-60 years old. Serum concentrations of TSH, T4, T3 and T3-Uptake were estimated by using Vitek Immuno Diagnostic assay System (VIDS). TSH values slightly increase with aging, but without significant changes. Mean T4 Values for females over age 40 years were significantly lower than younger women. Mean serum T3 declined with increasing age, but, also without a significant change. Values for T3U in females after age 40 years were significantly higher than females under age 40 years. The physiologic reasons for these findings may be due to sex-related changes in binding proteins and alteration in metabolic clearance rates, production, and degradation of these hormones with increasing age. Key words:-Thyroid stimulating hormone, thyroxine, triiodothrynine, T3Uptake, age, healthy females.